THE INFLUENCE OF BRAND IMAGE, BRAND TRUST AND CUSTOMER SATISFACTION ON BRAND LOYALTY (CASE OF SAMSUNG SMARTPHONE) - Pratiwi, Detha Misgi (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT The marketing environment has turn out to be a very multifaceted and competitive one and day by day marketing environment is shifting and developing gradually. Thus, it has become essential for business to look for ways of gaining and maintaining brand loyalty by building consumer believes, brand image and customer satisfaction. The study aims to identify the influence of brand image, brand trust and customer satisfaction on brand loyalty. 50 Samsung smartphone users in Manado were surveyed as respondents. The finding shows that brand image, brand trust and customer satisfaction have significant influence on brand loyalty simultaneously. While partially, only customer satisfaction has significant influence on brand loyalty, whereas brand image and brand trust does not have any significant influence on brand loyalty. Samsung should create consumer trust toward brand because brand trust is an important factor to make the consumer loyal with that brand. Â  Keywords: Brand Image, Brand Trust, Customer Satisfaction, Brand Loyalty.